Ethnic Disparities in Treatment of Chronic Pain in Individuals with Parkinson's Disease Living in the United Kingdom. Issue 3 (9th March 2022) - Rukavina, Katarina; Ocloo, Josephine; Skoric, Magdalena Krbot; Sauerbier, Anna; Thomas, Omotola; Staunton, Juliet; Awogbemila, Olabisi; Trivedi, Dhaval; Rizos, Alexandra; Chaudhuri, K. Ray
ABSTRACT: Background: Over 80% people with Parkinson's disease (PD; PwP) live with chronic pain. Objective: Whether ethnic disparities in receipt of appropriate analgesia exist among PwP with chronic pain living in the United Kingdom (UK). Methods: A retrospective datamining of an existing King's PD Pain Questionnaire validation study dataset enrolling 300 PwP. Results: 69 PwP: 23 Black (57% female), 23 Asian (57% female) and 23 White (65% female) had similar pain burden on the King's PD Pain Scale. Significantly more White PwP (83%) received pain relief compared to Black (48%) and Asian (43%) PwP ( p = 0.016). The difference was most evident for opioid analgesics (White 43% vs. Black 4% vs. Asian 4%, p ≤ 0.001). Conclusions: Ethnic disparities in the analgesic use among PwP with chronic pain living in the UK are evident in this retrospective analysis, prompting large‐scale studies and reinforcement of interventions to tackle the impact ethnicity might have on the successful analgesia.